2019
DOI: 10.1155/2019/4848279
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cells Promote the Differentiation of Adult Liver Hematopoietic Stem and Progenitor Cells into Lymphocytes via ICAM-1 and LFA-1 Interaction

Abstract: It has been reported that the adult liver contains hematopoietic stem and progenitor cells (HSPCs), which are associated with long-term hematopoietic reconstitution activity. Hepatic hematopoiesis plays an important role in the generation of cells involved in liver diseases. However, how the progenitors differentiate into functional myeloid cells and lymphocytes in the liver microenvironment remains unknown. In the present study, HSPC transplantation experiments were used to confirm that adult murine liver HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
(55 reference statements)
0
8
0
Order By: Relevance
“… 32 Similar to the thymus and small intestine, the liver microenvironment supports hematopoiesis and lymphocyte differentiation by secreting hematopoiesis-promoting cytokines, such as IL-7 and SCF. 12 , 38 Whether liver-specific LSM cells can differentiate into intrahepatic γδ T cells in situ remains unknown. In the present study, based on the scRNA-seq analysis, we found that γδ T precursor cells (C3-T/L) exist not only in the thymus but also in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 Similar to the thymus and small intestine, the liver microenvironment supports hematopoiesis and lymphocyte differentiation by secreting hematopoiesis-promoting cytokines, such as IL-7 and SCF. 12 , 38 Whether liver-specific LSM cells can differentiate into intrahepatic γδ T cells in situ remains unknown. In the present study, based on the scRNA-seq analysis, we found that γδ T precursor cells (C3-T/L) exist not only in the thymus but also in the liver.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Adult liver HSPCs have also been reported to differentiate into T and B lymphocytes. 12 More recent studies have focused on the developmental origins of γδ T cells and related transcriptional programs. 13 , 14 However, the precise developmental program, particularly the origins and extrathymic developmental pathways associated with liver γδ T cells, remains largely unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…These alterations may be caused by a lack of CD11d/CD18 expression in the thymus resulting in inaccurate T cell development. The overall importance of β2 integrins for the expansion of HPSC (hematopoietic stem and progenitor cells) was demonstrated in a study by Meng and co-workers [80]. In a coculture system of HSPCs and Kupffer cells, that constitute the liver-resident macrophage population [81], Kuppfer cells promoted HSPC expansion and differentiation to lymphocytes.…”
Section: Cell Differentiationmentioning
confidence: 94%
“…Some of these genes could directly affect NAFLD development, and the others may influence NAFLD by some related effects. The level of ICAM1 was markedly enhanced after the stimulation of lipopolysaccharide in the liver, and the blockade of it may destroy the cells’ adhesion and expansion ( Meng et al, 2019 ). CD44 , is proved to be of great significance in non-alcoholic steatohepatitis.…”
Section: Discussionmentioning
confidence: 99%